PENGARUH INTERAKSI KETIDAKPASTIAN LINGKUNGAN, DESENTRALISASI, DAN AGREGAT INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL - Dwirandra, A.A.N.B. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007), 2007)
This three-variate model of study is aimed to test whether variables ofenvironment uncertainty perceptions, decentralization, and aggregate of managerialaccounting information affect the performance of management. This study replicatesprevious studies to check the results consistency of the studies when they areimplemented in star-hotel industry which involve managers’ multicultural interaction.The qualitative primary data is collected using questionnaires developed byMahoney, Jerdee, and Carroll (1983) for managerial performance variable,Govindarajan (1986) for variable of environment uncertainty, Gul and Chia (1994) forvariable of decentralization, and Chenhall and Morris (1986) for variable aggregate ofmanagerial accounting information. The instruments have been tested and all are validand reliable. Non response bias tests have also been conducted and show that there areno significant differences between respondents who respond and those who do not. Thestudy uses partial derivation analysis of multiple regression model implemented bySchoonhoven (1981) and Govindarajan (1986).The results support all hypothesis which conclude that: (1) interaction ofenvironment uncertainty, decentralization, and aggregate of managerial accountinginformation affect managerial performance, (2) interaction of high degree ofdecentralization and wide scope of managerial accounting information system affectnegatively performance of managers who perceive low for environment uncertainty,and (3) interaction of high degree of decentralization and wide scope of managerialaccounting information system affect positively performance of managers who perceivehigh for environment uncertainty. The main implication of this study is that it isnecessary to consider degree of decentralization and perception of environmentuncertainty of users of information in designing managerial accounting system in orderto improve managers’ performances.
Keywords: perception of environment uncertainty, decentralization, aggregate of information, managerial performance, partial derivation